2002
DOI: 10.1109/tns.2002.1039654
|View full text |Cite
|
Sign up to set email alerts
|

CdTe stacked detectors for gamma-ray detection

Abstract: We describe a stacked detector made of thin cadmium telluride (CdTe) diode detectors. By using a thin CdTe device, we can overcome the charge loss problem due to the small mobility and short lifetime of holes in CdTe or cadmium zinc telluride (CdZnTe) detectors. However, a CdTe detector with a thickness of more than 5 mm is needed for adequate detection efficiency for gamma-rays of several hundred keV. Good energy resolution and good peak detection efficiency are difficult to obtain using such a thick CdTe det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…According to the analysis based on Monte Calro detector simulation, we confirmed the contribution of Doppler broadening is 2.6 degree, and the contributions from position resolution and energy resolution are 2.6 degree and 2.7 degree, respectively [29] Additionally, CdTe layers can also be used as scatterer if the energy of incident gamma-rays is high. According to our measurements, the obtained angular resolution is 35.9 degree at 122 keV, and 12.2 degree at 511 keV, which is mainly dominated by the effect of Doppler broadening [31]. When kinetic energy of an electron is above ∼ 250 keV, the range of electrons in silicomn exceeds the thickness of one layer of the DSSD (300 μm).…”
Section: Semiconductor Compton Telescopementioning
confidence: 67%
See 1 more Smart Citation
“…According to the analysis based on Monte Calro detector simulation, we confirmed the contribution of Doppler broadening is 2.6 degree, and the contributions from position resolution and energy resolution are 2.6 degree and 2.7 degree, respectively [29] Additionally, CdTe layers can also be used as scatterer if the energy of incident gamma-rays is high. According to our measurements, the obtained angular resolution is 35.9 degree at 122 keV, and 12.2 degree at 511 keV, which is mainly dominated by the effect of Doppler broadening [31]. When kinetic energy of an electron is above ∼ 250 keV, the range of electrons in silicomn exceeds the thickness of one layer of the DSSD (300 μm).…”
Section: Semiconductor Compton Telescopementioning
confidence: 67%
“…Taking advantage of significant progress in CdTe technology, we are developing a new generation of Compton telescope, the semiconductor Compton telescope [8,22,[29][30][31]. In addition to the low background capability by utilizing the Compton kinematics, it features high spectral resolution (2 keV (FHWM) at 100 keV) and high angular resolution close to the theoretical limit defined by the Doppler broadening.…”
Section: Semiconductor Compton Telescopementioning
confidence: 99%
“…In our previous studies, we demonstrated that both good energy resolution and good detection efficiency can be achieved with the CdTe stack detector. These were achieved using planar CdTe diode detectors with a thickness of 0.5 mm [16][17][18]. As the absorber detector of the Compton camera, three-dimensional position detection capabilities are necessary in addition to good energy resolution and good detection efficiency.…”
Section: Cdte Stack Detector As the Absorber Detector For The Comptonmentioning
confidence: 99%
“…A number of publications reported that employment of such technique increased the detector sensitivity in the high-energy range [7,8,16]. It is apparent that the radiation reaches the second detector being attenuated in conformity with the transmission of the metal electrode and the substrate of the first detector:…”
Section: Stacked Detectormentioning
confidence: 99%
“…4. Calculations were made for a detector with a different number of stacks up to 40 (the 40-stacked detector is reported in [16]). As it was initially assumed, increase in the detection efficiency of the stacked detector is observed only for the photon energy higher than ~100 keV.…”
Section: Stacked Detectormentioning
confidence: 99%